Optimalisasi Penguatan Karakter Santri Melalui Kegiatan Intrakulikuler di Pondok Pesantren - Azizah Nur Aini; Ali Rohmad (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Concern about the decline in ethics, morals and morals in Indonesia which has a negative impact on society. Strengthening character is considered the right solution to overcome this problem, with a focus on formal or non-formal education, including Islamic boarding schools. This research aims to determine character strengthening through Sabilul Competition activities at the Sabilul Muttaqin Islamic Boarding School, Mojokerto City. The characters studied include self-confident character, character who appreciates achievement, and productive character. The method used in this research is a qualitative descriptive method with data collection techniques through observation, interviews and documentation. The results of the research show that the students' confident character is formed because of their courage in participating in various competitions with confidence in their abilities. The character of appreciating achievements is shown by the support between friends and the ability to accept defeat. The productive character can be seen from the students' participation in competitions in their free time. Sabilul Competition activities at the Sabilul Muttaqin Islamic Boarding School are held at the end of every month on Thursday in the hall of the women's Islamic boarding school.